2008
DOI: 10.1227/01.neu.0000320382.21577.8e
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the Met Allele of the Brain-Derived Neurotrophic Factor Val66met Polymorphism to Memory After Aneurysmal Subarachnoid Hemorrhage

Abstract: As a whole, the BDNF Val66Met polymorphism was not associated with learning and memory performance in patients recovering from SAH. However, the Met allele might predict poor memory function among patients with SAH not complicated by a cerebral infarction. These findings support earlier reports of an association between the Met allele and low memory performance. Longitudinal studies comparing functional recovery from SAH between Met and Val/Val patients without cerebral infarctions are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 16 publications
2
19
0
1
Order By: Relevance
“…Variations in tumor necrosis factor-a, insulin-like growth factor 1, and brain-derived neurotrophic factor polymorphisms have been linked in some [27][28][29] but not all studies to outcome after SAH [30]. Nitric oxide produced by endothelial nitric oxide synthase prevents thrombosis and polymorphisms in this enzyme and in fibrinolytic enzymes that have been associated with DIND and outcome after SAH also could affect the response to SIRS [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Variations in tumor necrosis factor-a, insulin-like growth factor 1, and brain-derived neurotrophic factor polymorphisms have been linked in some [27][28][29] but not all studies to outcome after SAH [30]. Nitric oxide produced by endothelial nitric oxide synthase prevents thrombosis and polymorphisms in this enzyme and in fibrinolytic enzymes that have been associated with DIND and outcome after SAH also could affect the response to SIRS [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Identified as the first genetic alteration in the neurotrophin system, the BDNF has been implicated in conferring susceptibility to various neuropsychiatric disorders and altered episodic memory in patients with psychiatric disease (Sklar et al, 2002; Egan et al, 2003; Sen et al, 2003). Although studies on the impact of the BDNF polymorphism in the outcome after ischemic stroke are limited, clinical studies suggest a correlation of this BDNF polymorphism with poor outcome in hemorrhagic stroke patients (Siironen et al, 2007; Vilkki et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BDNF is involved in the pathophysiology of SAH. For example, clinical evidence has shown that a BDNF polymorphism is associated with poor patient recovery from SAH (40, 41). Animal experiments have demonstrated that exogenous BDNF infusion or upregulation of its expression improves neurobehavioral outcomes after SAH (42, 43).…”
Section: Discussionmentioning
confidence: 99%